Autoantibodies in heart failure and cardiac dysfunction - Kaya, Ziya; Leib, Christoph; Katus, Hugo (Circulation research, 2012)
Human heart failure is a disease with multifactorial causes, considerable morbidity, and high mortality. Several circulating autoantibodies, some of them being heart-specific, play a crucial role in the progression and induction of heart failure. However the precise mechanisms on how these autoantibodies perpetuate or even induce an organ specific autoimmune response are not yet fully understood. Also it is being a matter of current research to elucidate a potential pathophysiological role of the innate immune system in generating auto-reactive antibodies. In this review we will summarize the current available literature on circulating autoantibodies which are related to human heart failure. We will present clinical and animal studies that demonstrate the occurrence and pathophysiological relevance of several autoantibodies in heart failure, as well as point out biological mechanisms on molecular and cellular level. Finally the beneficial therapeutic effects of numerous clinical studies that target the hu...
Originally published: January 6, 2012
Gesehen am 30.07.2018